Physical and Acoustical Properties of Corn Husk Fiber Panels - Sari, Nasmi Herlina; Wardana, I. N. G.; Irawan, Yudy Surya; Siswanto, Eko (Advances in Acoustics and Vibration, 2016)
This research focuses on the development of a sustainable acoustic material comprising natural fibers of corn husk that were alkali modified by 1%, 2%, 5%, and 8% NaOH. The morphology and the acoustical, physical, and mechanical properties of the resulting fibers were experimentally investigated. Five different types of sample were produced in panel form, the acoustical properties of which were studied using a two-microphone impedance tube test. The porosity, tortuosity, and airflow resistivity of each panel were investigated, tensile tests were conducted, and the morphological aspects were evaluated via scanning electron microscopy. The sound absorption and tensile properties of the treated panels were better than those of raw fiber panels; the treated panels were of high airflow resistivity and had low porosity. Scanning electron micrographs of the surfaces of the corn husk fibers revealed that the different sound absorption properties of these panels were due to roughness and the lumen structures.